A single-cell analysis of intrinsic connectivity in the rat globus pallidus. - Sadek, A; Magill, P; Bolam, J (2007)
GABAergic neurons of the globus pallidus (GP) play critical roles in basal ganglia function by virtue of their widespread axonal projections to all parts of the basal ganglia. They also possess local axon collaterals. In view of the importance of GABAergic inputs in sculpting neuronal activity, we quantitatively characterized the local axon collaterals of individual GP neurons by in vivo recording, juxtacellular labeling, reconstruction, and light and electron microscopic analysis in the rat. All labeled GP neurons had similar firing properties and gave rise to local axon collaterals, the main synaptic targets of which were perikarya and primary dendrites. The neurons could be divided into two populations; neurons located within approximately 100 microm of the striatopallidal border ("outer" neurons), which possess a mean of 264 local axonal boutons, and those located approximately 100 microm or more from the striatopallidal border ("inner" neurons), which possess a mean of 581 local axonal boutons. The local axon collaterals gave rise to arborizations close to, or within, the parent dendritic field and arborizations located caudal, medial, and ventral to the parent neuron. The qualitative and quantitative differences in the connectivity of neurons located in the outer and inner regions of the GP underlie a complex microcircuitry that follows an asymmetric rostral to caudal organization. These data suggest that the GP should no longer be considered as an homogeneous relay nucleus that simply transmits striatal information to the subthalamic nucleus and basal ganglia output nuclei, but rather as a structure that can perform complex computations within its borders.